Impaired Vitamin D Signaling in T Cells From a Family With Hereditary Vitamin D Resistant Rickets - Al-Jaberi, Fatima A. H.; Kongsbak-Wismann, Martin; Aguayo-Orozco, Alejandro; Krogh, Nicolai; Buus, Terkild B.; Lopez, Daniel V.; Rode, Anna K. O.; Gravesen, Eva; Olgaard, Klaus; Brunak, Søren; Woetmann, Anders; Ødum, Niels; et al. (Frontiers in Immunology, 2021)
The active form of vitamin D, 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), mediates its immunomodulatory effects by binding to the vitamin D receptor (VDR). Here, we describe a new point mutation in the DNA-binding domain of the VDR and its consequences for 1,25(OH)2D3 signalling in T cells from heterozygous and homozygous carriers of the mutation. The mutation did not affect the overall structure or the ability of the VDR to bind 1,25(OH)2D3 and the retinoid X receptor. However, the subcellular localization of the VDR was strongly affected and the transcriptional activity was abolished by the mutation. In heterozygous carriers of the mutation, 1,25(OH)2D3-induced gene regulation was reduced by ~ 50% indicating that the expression level of wild-type VDR determines 1,25(OH)2D3 responsiveness in T cells. We show that vitamin D-mediated suppression of vitamin A-induced gene regulation depends on an intact ability of the VDR to bind DNA. Furthermore, we demonstrate that vitamin A inhibits 1,25(OH)2D3-induced translocation of the VDR to the nucleus and 1,25(OH)2D3-induced up-regulation of CYP24A1. Taken together, this study unravels novel aspects of vitamin D signalling and function of the VDR in human T cells.